1990
DOI: 10.2134/agronj1990.00021962008200030009x
|View full text |Cite
|
Sign up to set email alerts
|

Responses of a Perennial Grass‐Legume Mixture to Applied Nitrogen and Differing Soil Textures

Abstract: Sustained productivity in multiple‐species, perennial grass‐legume pastures depends in part on achieving and maintaining an appropriate species (SP) balance. Nitrogen levels for the grass component and consistent opportunity for rooting and nodulation of new legume stolons are important. Using an outdoor pot experiment, this study investigated perennial regrowth responses of orchardgrass (Dactylis glomerata L.), perennial ryegrass (Lolium perenne L.), ladino clover (Trifolium repens L.) and strawberry clover (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2017
2017

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 8 publications
0
2
0
Order By: Relevance
“…Kanyama‐Phiri et al . () reported that the proportion of ladino clover and orchardgrass ( Dactylis glomerata L.) in mixtures gradually decreased and increased, respectively, as N level increased. They showed that successive three‐split applications of 180 ton km −2 year −1 of N are useful in managing grass‐legume balance near 1:1.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Kanyama‐Phiri et al . () reported that the proportion of ladino clover and orchardgrass ( Dactylis glomerata L.) in mixtures gradually decreased and increased, respectively, as N level increased. They showed that successive three‐split applications of 180 ton km −2 year −1 of N are useful in managing grass‐legume balance near 1:1.…”
Section: Introductionmentioning
confidence: 99%
“…Nitrogen, which is often a limiting factor in soil, may aid the establishment of both grass and legumes (Laberge et al 2005;Kim and Sung 2009). Kanyama-Phiri et al (1990) reported that the proportion of ladino clover and orchardgrass (Dactylis glomerata L.) in mixtures gradually decreased and increased, respectively, as N level increased. They showed that successive three-split applications of 180 ton km À2 year À1 of N are useful in managing grass-legume balance near 1:1.…”
Section: Introductionmentioning
confidence: 99%